Material de referencia piloto: solución calibrante de Fe - JULIANA SERNA SAIZ; DIEGO ALEJANDRO AHUMADA FORIGUA; JOHANNA PAOLA ABELLA GAMBA; Serna Saiz, Juliana (Instituto Nacional de Metrología - INM, 2016)
Material de referencia piloto: solución calibrante de Fe